Neoadjuvant Chemotherapy Use in Bladder Cancer: A Survey of Current Practice and Opinions - N. G. Cowan; Y. Chen; T. M. Downs; B. H. Bochner; A. B. Apolo; M. P. Porter; J. C. La Rochelle; C. L. Amling; T. M. Koppie (Advances in Urology)
Objectives. Level 1 evidence supports the use of neoadjuvant chemotherapy (NAC) to improve overall survival in muscle invasive bladder cancer; however utilization rates remain low. The aims of our study were to determine factors associated with NAC use, to more clearly define reasons for low utilization, and to determine the current rate of NAC use among urologic oncologists. Materials and Methods. Active members of the Society for Urologic Oncology were provided a 20-question survey. Descriptive statistical analysis was conducted for each question and univariate analysis was performed. Results. We achieved a response rate of 21%. Clinical T3/T4 disease was the most often selected reason for recommending NAC (87%). Concerns with recommending NAC were age and comorbidities (54%) followed by delay in surgery (35%). An association was identified between urologic oncologists who discussed NAC with >90% of their patients and medical oncologists “always” recommending NAC (P=0.0009). NAC utilization rate was between 30 and 57%. Conclusions. Amongst this highly specialized group of respondents, clinical T3-T4 disease was the most common reason for implementation of NAC. Respondents who frequently discussed NAC were more likely to report their medical oncologist always recommending NAC. Reported NAC use was higher in this surveyed group (30–57%) compared with recently published rates.